1993
DOI: 10.1073/pnas.90.2.527
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the two nonallelic proinsulin genes in the developing mouse embryo.

Abstract: In the mouse, insulin is produced from two similar but nonallelic genes that encode proinsulins I and II. We have investigated expression of these two genes during mouse embryonic development, using a PCR to detect the two gene transcripts and immunocytochemistry to visualize the two corresponding proteins. At appearance of the dorsal pancreatic anlage at day 9.5 of gestation, both mRNAs could be detected in the embryos, and both proteins were present together in the same cells of the developing pancreas. At d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
146
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(150 citation statements)
references
References 31 publications
(35 reference statements)
3
146
0
1
Order By: Relevance
“…Our results imply that, under conditions of stimulation, the difference between rat insulin promoters I and II depends on Maf regulation. It has been reported that mouse insulin promoters I and II are also differentially regulated [35,36]. Since the RIPE3b elements of both genes are identical, other elements except for RIPE3b may be responsible for the regulational difference between mouse insulin promoters I and II.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results imply that, under conditions of stimulation, the difference between rat insulin promoters I and II depends on Maf regulation. It has been reported that mouse insulin promoters I and II are also differentially regulated [35,36]. Since the RIPE3b elements of both genes are identical, other elements except for RIPE3b may be responsible for the regulational difference between mouse insulin promoters I and II.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we indicated that MafA and MafB activate the RIPII and bind to the core site of RIPE3b. Mouse and rat possess two insulin promoters each (insulin promoters I and II), whereas human possesses only one promoter; these insulin promoters have unique transcriptional regulations [33][34][35][36]. Two significant differences appeared when the RIPE3b sequences of these insulin promoters were aligned with the MARE sequence (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other likely MafA-responsive genes, such as pdx-1 (28) and insulin I, were not activated effectively. Differences in the cis-element organization between the rodent insulin genes presumably limits the MafA responsiveness of insulin I because mouse insulin I and II are expressed independently and distinctly during development in the pancreas and thymus (29). In addition, glucagon expression was not influenced by MafA, suggesting that it does not interfere in ␣ cell-enriched MafB-mediated activation (ref.…”
Section: Resultsmentioning
confidence: 99%
“…Growth and morphogenesis of the bud epithelium leads to a ramification of small ductules containing the precursor cells of the acini, ducts, and islets of Langerhans, the major differentiated tissues of the mature pancreas (7,8). The islets form from dividing cells that escape the ductule epithelium, migrate through the surrounding mesenchyme, coalesce into endocrine cell masses, and differentiate into the four major islet cell types (8,9). The majority of the dividing cells remain within the ductule epithelium and differentiate into either acinar cells, which synthesize digestive hydrolytic enzymes, or mature duct cells, which secrete the fluid that transports the digestive enzymes to the intestine.…”
mentioning
confidence: 99%